Relationship Between Self-Efficiency And Learning Interest With Student’s Learning Achievement - Isti Munawaroh (Prosiding University Research Colloquium, 2021)
This study aims to determine the relationship between self-efficacy and interest inlearning with student achievement. The research was conducted on students of SDN 1Mranggen.This research is a type of correlational research. Research subjects wereselected using purposive sampling technique. The samples taken were 71 high schoolstudents. The method of data collection was done by using a closed questionnaire. Theinstrument validity test was conducted using the product moment formula while thereliability test used the Cronbach alpha formula with the help of SPSS. The analysisprerequisite test consisted of normality test, multicollinearity test, heteroscedasticity test,autocorrelation test and linearity test. Data analysis used parametric statisticaltechniques, namely simple regression test and multiple regression test with the help ofSPSS.The results showed that: (1) There was a relationship between self-efficacy andstudent achievement at SDN 1 Mranggen with the regression equation Y = 0.160x +64.992, R2 of 0.599 and a significance of 35%. (2) There is a positive relationship betweeninterest in learning and student achievement at SDN 1 Mranggen with the regressionequation Y = 0.199x + 65.315, R2 of 0.576 and a significance of 33%. (3) There is a positiverelationship between self-efficacy and interest in learning with student achievement atSDN 1 Mranggen with the regression equation Y = 0.102x1 + 0.098x2 + 63,152, R2 of 0.625and a significance of 39%.